Mechanistic Impact of Zinc Deficiency in Human Development - Hussain, Azhar; Jiang, Wenting; Wang, Xiukang; Shahid, Shumaila; Saba, Noreena; Ahmad, Maqshoof; Dar, Abubakar; Masood, Syed Usama; Imran, Muhammad; Mustafa, Adnan (Frontiers in Nutrition, 2022)
Zinc (Zn) deficiency in humans is an emerging global health issue affecting approximately two billion people across the globe. The situation prevails due to the intake of Zn deficient grains and vegetables worldwide. Clinical identification of Zn deficiency in humans remains problematic because the symptoms do not appear until impair the vital organs, such as the gastrointestinal track, central nervous system, immune system, skeletal, and nervous system. Lower Zn body levels are also responsible for multiple physiological disorders, such as apoptosis, organs destruction, DNA injuries, and oxidative damage to the cellular components through reactive oxygen species (ROS). The oxidative damage causes chronic inflammation lead toward several chronic diseases, such as heart diseases, cancers, alcohol-related malady, muscular contraction, and neuro-pathogenesis. The present review focused on the physiological and growth-related changes in humans under Zn deficient conditions, mechanisms adopted by the human body under Zn deficiency for the proper functioning of the body systems, and the importance of nutritional and nutraceutical approaches to overcome Zn deficiency in humans and concluded that the biofortified food is the best source of Zn as compared to the chemical supplementation to avoid their negative impacts on human.